Accident Analysis in Relation to Main Roof Structure When Longwall Face Advances toward a Roadway: A Case Study - Chang Liu; Zengqiang Yang; Peilin Gong; Kai Wang; Xiaoqiang Zhang; Junwen Zhang; Yulin Li (Advances in Civil Engineering)
Practices show that hydraulic supports crushing accidents or roadway supports failure often take place when a longwall face advances toward an abandoned roadway or a predriven equipment recovery room. Therefore, a 2D similar simulation experiment is conducted to reveal the loading mechanism. The result shows that when the workface advances close to roadways, the main roof breaks ahead of the workface and leads to instability of higher strata. These two changes induce a sharp increase of the load on supports and lead to an accident. Thus, more attention should be paid to the advanced fracture. Therefore, mechanical analysis is used to explain the advanced fracture. Results show that the failure of coal pillar being excavated induces a sharp increase in the main roof’s hanging length. Once the hanging length reaches the limit, the advanced fracture takes place. Therefore, the stability of the coal pillar and the hanging length of roof strata are two key factors that may induce an accident. To prevent the a similar supports crushing accident, the partial backfilled technology which partly backfills the abandoned roadway in height and length to maintain the stability of the coal pillar is put forward and put into practice. The field test shows a good effect.